Trends in developing metaheuristics, algorithms, and optimization approaches - Yin, Peng-Yeng, 1966- (Information Science Reference, 2013)
"This book provides insight on the latest advances and analysis of technologies in metaheuristics computing, offering widespread coverage on topics such as genetic algorithms, differential evolution, and ant colony optimization"--Vydavatelská anotace
"Premier reference source"--Z obálky
Keywords: heuristika; algoritmy (programování); počítačová simulace; kombinatorická optimalizace; umělá inteligence; heuristic; computer algorithms; computer simulation; combinatorial optimization; artificial intelligence; sborníky; elektronické knihy; papers of several authors; electronic books